2014
DOI: 10.1074/jbc.m113.543728
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Membrane Protein-2 (EMP2) Activates Src Protein and Is a Novel Therapeutic Target for Glioblastoma

Abstract: Background: EMP2 is a tetraspan protein linked with aggressive disease. Results: EMP2 correlates with activated Src in patients with GBM. Using intracranial mouse models, EMP2 promotes tumor cell invasiveness. Antibodies to EMP2 reduce GBM tumor load. Conclusion: EMP2 is a novel therapeutic target in GBM. Significance: The clinical outcome for patients with GBM remains poor, and thus new targeted therapies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 50 publications
1
55
0
Order By: Relevance
“…Being a member of the tetraspan protein superfamily, EMP2 is known to interact with and regulate a number of important cell adhesion and cell signaling molecules, such as b1 integrin, 4 FAK, and Src, 31,32 which are also known to play important roles in podocytes. The mechanisms by which expression and activity of these proteins are affected by EMP2 deletion and how it subsequently influences podocyte function and health deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Being a member of the tetraspan protein superfamily, EMP2 is known to interact with and regulate a number of important cell adhesion and cell signaling molecules, such as b1 integrin, 4 FAK, and Src, 31,32 which are also known to play important roles in podocytes. The mechanisms by which expression and activity of these proteins are affected by EMP2 deletion and how it subsequently influences podocyte function and health deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-EMP2 antibody therapy successfully decreased tumor load in subcutaneous mouse models and enhanced GBM cell death in vitro . 90 These results suggest anti-EMP2 therapy may be of value in the pathogenesis of GBM.…”
Section: Emps (Emp1 Emp2 and Emp3)mentioning
confidence: 92%
“…This has been shown in both epithelial tumors of the uterus and breast, as well as in primary CNS malignancies. 11,52,53 As such, targeting EMP2 would be predicted to reduce FAK activation. Our laboratory has been instrumental in creating a panel of antibodies and antibody fragments to target EMP2, and we have shown that these reagents specifically localize to EMP2 positive tumors with minimal targeting to normal tissue, suggesting that EMP2 is normally sequestered.…”
Section: Fak Inhibitorsmentioning
confidence: 99%